English in a rural linguistic landscape of globalizing China - Liu, Guangxiang; Ma, Chaojun (English today, 2024)
Usually focusing on linguistic/semiotic signs in culturally and linguistically diverse communities, linguistic landscape (hereafter LL) has appeared as a methodological paradigm for the investigation of the representation and visibility of languages across geographical contexts (Landry & Bourhis, 1997; Scollon & Scollon, 2003). Highlighting the informative and symbolic functions of languages, this paradigm enables the combination of a quantitatively distributive lens with a refined ethnographic perspective to generate insights into the ethnolinguistic vitality of a given territory and the spread of international lingua francas – in most cases English – in localized settings (Backhaus, 2007; Jaworski & Thurlow, 2010; Li, 2015).